The Impact Of Financial Accounting Systems On Corporate Governance In Jordan - Sameer Ahmad Hmoud Al-amro (International Journal of Advanced Science and Technology, 2020)
This study was established to check the impact of financial accounting system on corporate governance in Jordan. As a result, the study showed that the four elements of financial accounting systems had a significant positive impact on corporate governance. Organizations with better bookkeeping systems adhered to most of the principles of corporate governance. They demonstrated higher commitment in upholding shareholder rights, disclosing information in a regular and timely manner, and enforcing internal controls in order to curb fraud. Similarly, a positive association was observed between the quality of financial reporting systems and corporate governance. Companies that had more comprehensive and reliable financial reporting systems were able to disclose more material information to the public, adhere to regulations and professional ethics, and respect shareholder rights. Thirdly, this study established a significant association between the quality of budgeting systems and the level of corporate governance. Efficient budgeting systems were associated with high quality of corporate governance. Finally, the results indicated that there was a significance association between adherence to relevant regulations and the level of corporate governance.